Utilization of nano-olive stones in environmental remediation of methylene blue from water - Mohammad A. Al-Ghouti (8882054) (2020)
Background The use of agricultural waste as a low-cost adsorbent for the removal of hazardous methylene blue (MB) from aqueous solution was investigated. In this research, the potentiality of using black nano olive stones (black NOS) and green nano olive stones (green NOS) for MB adsorption was conducted. Methods Various remediation parameters such as initial MB concentration, pH, and temperature were investigated. Thermodynamic study was carried out to determine the homogeneity of the adsorbent and spontaneity of the adsorption process. Different physical and chemical characterizations were studied using scanning electron microscopy (SEM), Fourier transform infrared (FTIR), Brunauer-Emmett-Teller (BET) surface area, pore radius and pore volume. Results It was found that NOS exhibits an acidic nature, however the highest MB removal efficiency was recorded at pH 10; reaching up to 71%. The negative value of the heat of the adsorption process (∆H ° ) indicated the reaction followed an exothermic pathway while the negative value of Gibbs adsorption (∆G ° ) further suggested its spontaneous nature. The results indicated that the Freundlich model described well the adsorption process with 99.5% correlation coefficient for green NOS. FTIR was used to analyze functional groups on the adsorbents’ surfaces that could play vital roles in the remediation process. SEM analysis revealed that the adsorbents comprised of abundant spherical deep cavities and porous nature. Conclusion The result obtained successfully demonstrated the potential of using black and green NOS as suitable adsorbents for the removal of MB from water. Other Information Published in: Journal of Environmental Health Science and Engineering License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s40201-019-00438-y